Associations of Environmental Conditions and Vibrio parahaemolyticus Genetic Markers in Washington State Pacific Oysters - Flynn, Aspen; Davis, Benjamin J. K.; Atherly, Erika; Olson, Gina; Bowers, John C.; DePaola, Angelo; Curriero, Frank C. (Frontiers in Microbiology, 2019)
Vibrio parahaemolyticus is a naturally occurring bacterium in estuarine waters and is a major cause of seafood-borne illness. The bacterium has been consistently identified in Pacific Northwest waters and elevated illness rates of vibriosis in Washington state have raised concerns among growers, risk managers, and consumers of Pacific oysters (Crassostrea gigas). In order to better understand pre-harvest variation of V. parahaemolyticus in the region, abundance of total and potentially pathogenic strains of the bacterium in a large number of Washington State Pacific oyster samples were compared with environmental conditions at the time of sampling. The Washington Department of Health regularly sampled oysters between June and September at over 21 locations from 2014 to 2018, resulting in over 946 samples. V. parahaemolyticus strains carrying three genetic markers, tlh, trh, and tdh, were enumerated in oyster tissue using a most probable number-PCR analysis. Tobit regressions and seemingly unrelated estimations were used to formally assess relationships between environmental measures and genetic markers. All genetic markers were found to be positively associated with temperature, independent of the abundance of other genetic markers. Surface water temperature displayed a non-linear relationship, with no association observed between any genetic marker in the warmest waters. There were also stark differences between surface and shore water temperature models. Salinity was not found to be substantially associated with any of the genetic variables. The relative abundance of tdh+ strains given total V. parahaemolyticus abundance (pathogenic ratio tdh:tlh) was negatively associated with water temperature in colder waters and decreased exponentially as total V. parahaemolyticus abundance increased. Strains carrying the trh gene had a pronounced positive association with strains carrying the tdh gene but was also negatively associated with the tdh:tlh pathogenic ratio. These results suggest that there are ecological relationships of competition, growth, and survival for V. parahaemolyticus strains in the oyster tissue matrix. This work also improves the overall understanding of environmental associations with V. parahaemolyticus in Washington state Pacific oysters, laying the groundwork for future risk mitigation efforts in the region.